Cover Image, Volume 86, Issue 5. Issue 5 (16th April 2018) - Teplyakov, Alexey; Obmolova, Galina; Luo, Jinquan; Gilliland, Gary L.
Abstract : The cover image, by Alexey Teplyakov et al., is based on the Short Communication Crystal structure of B‐cell co‐receptor CD19 in complex with antibody B43 reveals an unexpected fold, DOI:10.1002/prot.25485 .